Strategi Guru dalam Mengatasi Kesulitan Belajar Siswa pada Mata Pelajaran PAI di Sekolah Al-Farabi Sunggal - Mahisarani; Himmatul Fitria; Aisyah Purnama Siregar (Education & Learning, 2021)
When conducting research, the researcher has several simple goals, namely to find out what difficulties students experience when studying with teachers, then what are the strategies used by teachers in overcoming learning difficulties that afflict all students, especially those who attend SMP Al-Farbi Sunggal Deli Serdang. To facilitate data collection, the researchers themselves when conducting field research using qualitative research types in terms of phenomenology so that when taking data the researchers used observation, interviews, and documentation techniques. As for the main data source in this study, PAI teachers at SMP Al-Farabi Sunggal Deli Serdang, in terms of analyzing data, the steps used were data reduction, data presentation, and data verification. students are like fatigue in terms of reading the Qur'an, this is where a teacher must be wise in providing solutions to these students because if left alone it will have a bad impact on students in the future.